Relative abundance, habitat selection, and diet of the coyote in northern México - Álvarez-Córdova, Fernando; Fernández, Jesus A.; Camargo-Sanabria, Angela A.; Ontiveros, Juan C.; Titulaer, Mieke (THERYA, 2022)
The coyote (Canis latrans) is a widespread predator with a high degree of adaptation to different ecosystems. The objective of this study was to estimate the relative abundance index, habitat selection, and diet of C. latrans through scent stations, in two types of vegetation located in northwestern Chihuahua. From April 2018 to March 2019, ten fixed scent stations (SS) were placed in pine-oak forest and other ten in semi-open grassland, with a linear separation of 500 meters between each station to achieve a five km transect in each vegetation during 12 samplings (two sampling night per month) for totaling 420 SS after discarding inactive SS. The relative abundance index of coyote showed that both types of vegetation, pine-oak forest (0.30) and semi-open grassland (0.23) were used in a similar way. The habitat selection test (Chi2) showed that coyote abundance and type of vegetation were independent (Ï‡2 = 2.96, P > 0.05), not showing statistically significant differences in annual relative abundance index of coyotes between the two vegetation types. The food items detected in thirty-four scats collected belonged to mammals (55.9 %), fruits (35.3 %) and arthropods (8.8 %). Rodents and lagomorphs were the main source of food. Throughout the sampling period, the pine-oak forest showed the greatest relative abundance index of C. latrans. This may be because the forest provides them with shelter from climatic situations and a greater variety of seeds, fruits and insects. In this study the two seasons with the highest relative abundance were spring and autumn in both ecosystems, coinciding with an increase in rainfall, resulting in an abundance of potential prey (rodents and lagomorphs), and other food items like fruits. Regarding annual diet the most consumed prey were mammals. We found differences in diet between seasons, that can be explained by the variation in food availability among seasons.